2018
DOI: 10.1016/j.tranon.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Pathological, and Molecular Characteristics of CpG Island Methylator Phenotype in Colorectal Cancer: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: CpG island methylator phenotype (CIMP) tumors, comprising 20% of colorectal cancers, are associated with female sex, age, right-sided location, and BRAF mutations. However, other factors potentially associated with CIMP have not been robustly examined. This meta-analysis provides a comprehensive assessment of the clinical, pathologic, and molecular characteristics that define CIMP tumors. METHODS: We conducted a comprehensive search of the literature from January 1999 through April 2018 and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 163 publications
5
55
0
Order By: Relevance
“…Still it is clear from Table 6 that the stage-salient hypermethylated biomarkers identified in our study could constitute an aggregate novel CIMP. The CIMP has been associated with advanced T staging (T3/T4) [68], which accords with our finding of five hypermethylated stage IV-salient DMGs. Epigenetic intervention for CIMP-positive cancers has been suggested as a possible treatment strategy [69].…”
Section: Stage-iv Salient Dmgssupporting
confidence: 92%
“…Still it is clear from Table 6 that the stage-salient hypermethylated biomarkers identified in our study could constitute an aggregate novel CIMP. The CIMP has been associated with advanced T staging (T3/T4) [68], which accords with our finding of five hypermethylated stage IV-salient DMGs. Epigenetic intervention for CIMP-positive cancers has been suggested as a possible treatment strategy [69].…”
Section: Stage-iv Salient Dmgssupporting
confidence: 92%
“…Interestingly, 15-20% of human CRCs are characterized by the CpG-island methylator phenotype (CIMP), subdivided in CIMP-high (CIMP-H) and CIMP-low (CIMP-L) and this correlates with the MSI phenotype (19). Thus, the relationship between our 12-genes hypermethylated signature and CIMP status was evaluated in TCGA COAD dataset and in our in-house cohort according to Hinoue et al (20).…”
Section: Resultsmentioning
confidence: 99%
“…The Fusobacterium-CRC link was further strengthened, when Rezasoltani et al [30] found an enrichment of F. nucleatum in adenomatous polyps compared with healthy matched controls. Ultimately, in 2018, a meta-analysis which included 122 studies associated high F. nucleatum numbers with the tumorigenesis pathway and the CpG island methylator phenotype [49]. Over time, evidence has continued to accumulate about the relationship between F. nucleatum and CRC going beyond a correlation, with the species now being viewed as a causative agent.…”
Section: F Nucleatummentioning
confidence: 99%